Electrospun nanofibers in drug delivery: recent developments and perspectives. (April 2012) - Williams, Gareth R; Chatterton, Nicholas P; Nazir, Tahir; Yu, Deng-Guang; Zhu, Li-Min; Branford-White, Christopher J
In this review article, some key challenges in drug delivery are first introduced and methods that have been applied in attempts to solve them enumerated. Particularly intractable problems are highlighted: these include issues of solubility, targeting and drug degradation. The technique of electrospinning is subsequently introduced, and the influence of processing parameters on the fibers produced discussed. The potential of electrospun nanofibers in drug delivery is then explored, with examples given from the recent literature to illustrate how fibers can be used to overcome hurdles in drug solubility, degradation and targeting. Future perspectives and challenges are also considered.